Pediatric End of Life Care: Impact of Islamic Faith. (August 2022) - Hafez, Shahad A.; Snethen, Julia A.; Ngui, Emmanuel; Ellis, Julie; Taani, Murad
Studies investigating children and families' experiences at end of life in Saudi Arabia are limited. However, one factor found to have an impact on patient and primary caregiver end of life care is Islam. Since women are the primary caregivers for children in Saudi Arabia, the purpose of this study was to explore the perceptions of Muslim women caring for a child at end of life. Using a qualitative approach, interviews were conducted with 24 female primary caregivers caring for a child at end of life. Thematic analysis was used to analyze the data. The researchers found that Islamic beliefs and practices had a positive influence on primary caregivers' experiences. Islamic beliefs and practices helped support participants through their child's end of life experience. Results have implications for health care education, practice, policy, and future research on end of life in Saudi Arabia other Muslim countries.